Analisis Pendekatan Struktural Pada Puisi “Tanah” Karya Wiji Thukul (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Poetry is the poet's interpretation of life. The interpretation reflects the poet's view of the surrounding reality. Reading poetry is a literary art enjoyment. Poetry is a rich literature that can be used to express oneself from the author, for example in Widji Thukul's poem entitled "Land" which describes love and affection for the motherland, the struggle against injustice, and the spirit of resistance to existing oppression. The purpose of this analysis is to dissect the poem "Tanah" by Wiji Thukul structurally the structural approach in poetry refers to the analysis that is focused on structural elements in a poem. This approach aims to understand how these elements interact and contribute to the overall understanding of the poem.